Mapping of public health courses and training programs in Brazil - Peres, Frederico; Centurión, Maria Pasionaria Blanco; Silva, Juliana Monteiro Bastos da; Brandão, Ana Laura (Revista de Saúde Pública, 2023)
OBJECTIVE: To map public health courses and training programs in Brazil and identify, in their curricula and study plans, the level of linkage between the skills and competencies developed by them and the essential public health functions. METHODS: Descriptive, exploratory study based on collection and analysis of information available on the websites of educational institutions that offer public health courses and training programs in Brazil. Data was collected within the scope of the I Mapeo de Cursos y Programas de Formación en Salud Pública de América Latina. RESULTS: A total of 1,222 public health courses and training programs offered in the country were identified, with unequal territorial distribution but taking place in all federation units. Results revealed a set of challenges to public health professionals’ training, including lack of linkage both between training offer and demand in public health (unequal distribution of courses, concentration of training capacity in capitals and in certain regions, among others), and between theories and training practices (low levels of connection of developed skills and competencies with the essential public health functions, predominance of disciplinary method guided by professional competence centers, among others). CONCLUSIONS: Overcoming these challenges requires structural, political, and technological efforts, narrowing the gaps between public health training programs’ availability and the demands of health services and programs in the country.